Memahami Kode Phonetic Alphabet Pada Komunikasi Radio Marine - Pranata, Winny Rizal (Universitas Semarang, 2013)
This study purpose to understand and describe in detail and in-dept understanding of the meaning and the use of phonetic alphabet in radio marine communication. Theory used in this study is syimbolic interaksionisme that states when a movement in sociology focused to way people shape the meaning and structure of the community through conversations. The research method used is descriptive qualitative with interpretive perspective. This research was conducted PT. Pelabuhan Indonesia Scouting III Tanjung Emas Semarang with three (3) sample person as radio marine operator.In concluded for this study has answered phonetic alphabet code is a symbol that used to interaction tool for equalized and straighten meaning when there is misunderstanding in the delivery and reception of informationbetween both radio operator in radio marine communication especially PT. Pelabuhan Indonesia III Tanjung Emas Semarang to understand the meaning from the contents of the message to be effective communication.